2019
DOI: 10.6061/clinics/2019/e346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a bone cement-injectable cannulated pedicle screw augmented with polymethylmethacrylate: 128 osteoporotic patients with 42 months of follow-up

Abstract: OBJECTIVES: To evaluate the safety and efficacy of a novel bone cement-injectable cannulated pedicle screw augmented with polymethylmethacrylate in osteoporotic spinal surgery. METHODS: This study included 128 patients with osteoporosis (BMD T-score –3.2±1.9; range, –5.4 to –2.5) who underwent spinal decompression and instrumentation with a polymethylmethacrylate-augmented bone cement-injectable cannulated pedicle screw. Postoperative Visual Analogue Scale scores and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
16
0
3
Order By: Relevance
“…The biomechanical stability of pedicle screw xation systems is particularly important in patients with lumbar spondylolisthesis and osteoporosis (11,24). Studies have shown that the use of PMMAaugmented CPSs to reconstruct the displaced vertebral body and perform bony fusion is still the main surgical method for these patients (19,20,(24)(25)(26)(27)(28). Theoretically, more CPSs require a greater holding force by internal xation; however, overuse of CPSs may increase the risk of complications related to PMMA leakage, including allergic reactions, venous or pulmonary embolism, and di culty with revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomechanical stability of pedicle screw xation systems is particularly important in patients with lumbar spondylolisthesis and osteoporosis (11,24). Studies have shown that the use of PMMAaugmented CPSs to reconstruct the displaced vertebral body and perform bony fusion is still the main surgical method for these patients (19,20,(24)(25)(26)(27)(28). Theoretically, more CPSs require a greater holding force by internal xation; however, overuse of CPSs may increase the risk of complications related to PMMA leakage, including allergic reactions, venous or pulmonary embolism, and di culty with revision.…”
Section: Discussionmentioning
confidence: 99%
“…A suitable cage was lled with crushed autologous bone for fusion, then rods were installed and nuts were locked. In this study, a new type of PMMA-augmented CPS, named 'bone cement injectable cannulated pedicle screw (CICPS)' was developed by the authors for reduction and xation, a detailed introduction of which was reported in detail in previous studies (17)(18)(19)(20).…”
Section: Patientsmentioning
confidence: 99%
“…Lumbar spondylolisthesis with osteoporosis has great requirements for the biomechanical stability of pedicle screws xation system (11,24). Studies have shown that CPSs augmented by PMMA to reconstruct the displaced vertebral body and perform bony fusion is still the main surgical method for these patients (19,20,(24)(25)(26)(27)(28). Theoretically, the more CPSs used the greater holding force supplied by the internal xation.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports on the accurate and reasonable application guidelines of CPSs to improve the rationality in clinical practice. We reviewed the published literatures and fund that some studies using CPSs in bilateral sides (25)(26)(27)(28), while other studies using in unilateral side partially (17,19,20). Therefore, it has great clinically value to explore whether unilateral PMMA-augmented CPSs can provide adequate stability compared with bilateral PMMA augmentation, as well as whether any difference exist in the effectiveness and complications between the two methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation